Hubungan Usia, Masa Kerja dan Sikap Kerja dengan Keluhan Low Back Pain pada Nelayan - Rahayu, Sri; Daningrum, Dini; Wifdah, Siti Gisa’atul; Pratiwi, Wiwik Eko (Universitas Faletehan, 2024)
Fishermen are at risk of experiencing low back pain (LBP) due to the work process with repetitive movements. Most of them were recorded to have lower back pain. This study aims to determine the relationship between LBP complaints with age, length of service, and work attitudes of fishermen at the Karangantu Nusantara Fisheries Port, Serang City, Banten Province, Indonesia. The respondents were 78 fishermen who’s selected using the accidental sampling technique. The research design was cross-sectional. The data collection techniques were interviews and a questionnaire. The data was analyzed using chi square test. The results showed that 92% of respondents had a risky work attitude, 54% of respondents had a risky work duration over 18 years old, 50% of respondents were at risk at the age of over 39 years, and 85% of respondents had complaints of low back pain. The results of the analysis showed that age (P value 0.005), working period (P value 0.002), and work attitude (P value 0.000) were variables related to LBP complaints. The leaders of the Karangantu Nusantara Fisheries Port together with the local government and health workers were expected to provide education to fishermen about good postures when doing fishing activities to reduce complaints of lower back pain.